Capacitance Characterization of Elastomeric Dielectrics for Applications in Intrinsically Stretchable Thin Film Transistors. (9th May 2016) - Kong, Desheng; Pfattner, Raphael; Chortos, Alex; Lu, Chien; Hinckley, Allison C.; Wang, Chao; Lee, Wen‐Ya; Chung, Jong Won; Bao, Zhenan
Abstract : Stretchable electronics exhibit unique mechanical properties to expand the applications areas of conventional electronics based on rigid wafers. Intrinsically stretchable thin film transistor is an essential component for functional stretchable electronics, which presents a great opportunity to develop mechanically compliant electronic materials. Certain elastomers have been recently adopted as the gate dielectrics, but their dielectric properties have not been thoroughly investigated for such applications. Here, a charging measurement technique with a resistor–capacitor circuit is proposed to quantify the capacitance of the dielectric layers based on elastomers. As compared with conventional methods, the technique serves as a universal approach to extract the capacitance of various elastomers under static conditions, irrespective of the charging mechanisms. This technique also offers a facile approach to reliably quantify the mobility of thin film transistors based on elastomeric dielectrics, paving the way to utilize this class of dielectrics in the development of intrinsically stretchable transistors. Abstract : A charging measurement technique is introduced as a universal approach to quantify the capacitance of elastomeric dielectrics. It reveals elastomers may either behave as conventional rigid polymer dielectrics or solid‐state electrolyte, with distinctive capacitance values and scaling relations. The development allows the mobility values of corresponding thin film transistors to be accurately determined, which is essential for the development of instrinsically stretchable transistors.